Mutations in Severe, Type III von Willebrand’s Disease in the Dutch Population: Candidate Missense and Nonsense Mutations Associated with Reduced Levels of von Willebrand Factor Messenger RNA - Eikenboom, Jeroen C J; Ploos van Amstel, Hans K; Reitsma, Pieter H; Briët, Ernest (Thrombosis and Haemostasis, 1992)
The von Willebrand factor (vWF) genes of nine unrelated, severe, type III von Willebrand’s disease (vWD) patients (six of Dutch origin) and four unrelated Dutch type I vWD patients were screened for mutations in exons that contain CGA codons (Arg), which are liable to mutation to TGA stop codons. The nine exons of the vWF gene (3, 8, 9, 10, 28, 31, 32, 43 and 45) that contain all the CGA codons (11 in total) of the vWF cDNA were amplified by the polymerase chain reaction and screened for mutations by single-strand conformation polymorphism analysis, restriction enzyme – and/or nucleotide sequence analysis. Three of the severe vWD patients were found to be heterozygous for a nonsense mutation: CGA Arg 2535 → TGA Stop. Three other severe vWD patients were homozygous for a single nucleotide substitution, AAC Asn 2546 → TAC Tyr. The transcription of these mutated alleles was tested by cDNA dependent amplification of platelet RNA. The level of transcription product was strongly reduced for either mutant allele.